Antigenicity of cell wall mannans of Candida albicans NIH B-792 (serotype B) strain cells cultured at high temperature in yeast extract-containing sabouraud liquid medium. - Okawa, Y (1996)
Cultivation of Candida albicans NIH B-792 (serotype B) at high temperature (37 degrees C) for 48 h in yeast extract-containing Sabouraud liquid medium (YSLM) provided the following findings in comparison with the findings obtained after incubation at 27 degrees C. Growth of the blastoconidia of this strain was decreased, with a dry weight of 9%, and the cells were deficient in cytokinesis. The cells did not undergo agglutination with serum factor 5 from a commercially available serum factor kit (Candida Check). Mannan (B-37-M) obtained from the cells cultured at 37 degrees C had partially lost its reactivity against serum factor 4 and lost most of its reactivity against serum factor 5 in an enzyme-linked immunosorbent assay (ELISA) in contrast to that (B-27-M) at 27 degrees C. Both cells and mannan prepared by cultivation first at 37 degrees C and then at 27 degrees C entirely recovered their reactivities with serum factors 4 and 5. 1H-nuclear magnetic resonance analysis also revealed that B-37-M had lost a beta-1,2-linked mannopyranose unit and retained a phosphate group. Similar changes were observed in the three other serotype B strains used in the study. The beta-1,2-linked mannooligosaccharides longer than mannotetraose were not included among the products released from B-37-M by mild acid treatment. The results of the inhibition ELISA with a series of beta-1,2-linked mannooligosaccharides from biose to octaose (M2 to M8, respectively) showed that the reactivity against serum factor 4 was inhibited most strongly by the oligosaccharides M4 to M8 and that the reactivity against serum factor 5 was inhibited completely by relatively longer oligosaccharides, M5 to M8, indicating their participation as the antigenic factor 5 epitopes.